1992
DOI: 10.1002/qua.560420522
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence lifetime distribution of folded and unfolded proteins

Abstract: Time-resolved fluorescence of single tryptophan proteins have demonstrated the complexity of protein dynamic and protein structure. In particular, for some single tryptophan proteins, their fluorescence decay is best described by a distribution of fluorescence lifetimes rather than one or two lifetimes. Such results have provided further confirmation that the protein system is one which fluctuates between a hierarchy of many conformational substates. With this scenario as a theoretical framework, the correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…1). Gratton and coworkers [26–30]have demonstrated that the widths of the lifetime distributions recovered in the cases of single tryptophan proteins can be related to the extent of motion of the fluorophore, namely, decreasing as the rate of motion increases. Our observations show an increased rate of local mobility of Trp‐214 in FDH‐HSA and Met‐218 HSA over that of Trp‐214 in normal HSA and, hence, correlate well with the decreased widths of the recovered lifetime distributions for FDH‐HSA and Met‐218 HSA.…”
Section: Discussionmentioning
confidence: 99%
“…1). Gratton and coworkers [26–30]have demonstrated that the widths of the lifetime distributions recovered in the cases of single tryptophan proteins can be related to the extent of motion of the fluorophore, namely, decreasing as the rate of motion increases. Our observations show an increased rate of local mobility of Trp‐214 in FDH‐HSA and Met‐218 HSA over that of Trp‐214 in normal HSA and, hence, correlate well with the decreased widths of the recovered lifetime distributions for FDH‐HSA and Met‐218 HSA.…”
Section: Discussionmentioning
confidence: 99%
“…For fluorescence measurements, the BSA concentration was kept constant in all samples, while the complex concentration was increased from 3.125 to 150  μ M, and quenching of the emission intensity of the tryptophan residues of BSA at 320 nm (excitation wavelength 280 nm) was monitored at different temperatures (300 and 310 K). The experiments were carried out in triplicate and analyzed using the classical Stern-Volmer equationT1F0F=1+kqτoQ=1+KsvQ,where F 0 and F are the fluorescence intensities in the absence and presence of quencher, respectively, [ Q ] is the quencher concentration, and K sv is the Stern-Volmer quenching constant, which can be written asT1Kq=Ksvτo,where K q is the biomolecular quenching rate constant and τ o is the average lifetime of the fluorophore in the absence of quencher (6.2 × 10 −9  s) [20]. Therefore, (2) was applied to determine K sv by linear regression of a plot of F 0 / F versus [ Q ].…”
Section: Methodsmentioning
confidence: 99%
“…[Q] is the quencher concentration, and Ksv Stern-Volmer the quenching constant, which can be written as K q = K sv /τ o , where K q is the biomolecular quenching rate constant and τ o is the average lifetime of the fluorophore in the absence of quencher (6.2x10 -9 s) [26]. Therefore, Eq.…”
Section: Bsa-binding Experimentsmentioning
confidence: 99%